Notch signalling pathway as an oncogenic factor involved in cancer development - Brzozowa-Zasada, Marlena; Piecuch, Adam; Dittfeld, Anna; Mielańczyk, Łukasz; Michalski, Marek; Wyrobiec, Grzegorz; Harabin-Słowińska, Marzena; Kurek, Józef; Wojnicz, Romuald (Contemporary Oncology/Współczesna Onkologia, 2016)
Notch signalling is an evolutionarily conserved signalling pathway, which plays a significant role in a wide array of cellular processes including proliferation, differentiation, and apoptosis. Nevertheless, it must be noted that Notch is a binary cell fate determinant, and its overexpression has been described as oncogenic in a broad range of human malignancies. This finding led to interest in therapeutically targeting this pathway especially by the use of GSIs, which block the cleavage of Notch at the cell membrane and inhibit release of the transcriptionally active NotchIC subunit. Preclinical cancer models have clearly demonstrated that GSIs suppress the growth of such malignancies as pancreatic, breast, and lung cancer; however, GSI treatment in vivo is associated with side effects, especially those within the gastrointestinal tract. Although intensive studies are associated with the role of -secretase in pathological states, it should be pointed out that this complex impacts on proteolytic cleavages of around 55 membrane proteins. Therefore, it is clear that GSIs are highly non-specific and additional drugs must be designed, which will more specifically target components of the Notch signalling.